DATA-SHARING EN URUGUAY, LA VISIÓN DE LOS COLECTORES Y USUARIOS DE DATOS - Grattarola, Florencia; Pincheira-Donoso, Daniel (Boletín de la Sociedad Zoológica del Uruguay, 2019)
Data-sharing has become a key issue in modern science, with numerous advantages for both data collectors and user. However, the practice of sharing data in Uruguay is still uncommon given there are no primary biodiversity datasets open or publicly available. The reasons behind such low frequency of data availability are still unknown. This study explores the vision of data collectors and users analysing the reasons for both the reluctance to share data and the motivations for doing so. Over-all, scientists are willing to share their research data if they receive adequate credit for their effort and knowledge. In order to translate the will into an effective practice of open science, we must work on the incentives and motivation structures behind, communicate the importance and benefits of data openness and exchange, and provide technical tools on how to share. Importantly, data-sharing practice must result in the reinforce of a scientific collaboration culture that benefits not only researchers at the individual level, but the progress of knowledge itself. This work represents a valuable initial approach to the subject that proofs the importance that data availability has for researchers in Uruguay and the need for it to be mostly discussed.